A normative ethical analysis of Islamic unit-linked insurance using the Maqasid Shariah framework of Abu Zahrah - Kholis, Nur (Journal of Islamic Economics Lariba, 2025)
IntroductionIslamic unit-linked insurance (IULI) products are widely offered in Indonesia as financial instruments that integrate Shariah-compliant protection and investment features. While these products formally adhere to legal Shariah contracts, growing concerns have emerged regarding their operational alignment with Islamic ethical principles, particularly justice. Previous studies have focused on the legal structure of Islamic insurance, but few have assessed whether their practices fulfill the higher objectives of Islamic law (maqasid shariah), especially from a normative ethical perspective.ObjectivesThis study aims to evaluate the operational practices of Islamic unit-linked insurance in Indonesia through the lens of maqasid shariah as conceptualized by Abu Zahrah. It seeks to determine whether the structural compliance of IULI contracts also translates into ethical and social justice in practice, particularly in cost transparency, fund management, and participant equity.MethodUsing a normative qualitative approach, this study analyzed policy documents, fatwas issued by Indonesia’s Shariah authority, and cost structures of four major Islamic insurance providers. The analysis applied Abu Zahrah’s three-dimensional maqasid framework—spiritual integrity, justice, and public welfare—to assess the alignment between contract theory and actual implementation. Contractual, regulatory, and ethical aspects were examined in light of Islamic jurisprudence.ResultsThe study found that while the IULI contracts were formally Shariah-compliant, operational practices exhibited major ethical inconsistencies. These include disproportionate acquisition costs, ambiguous fund classification, and vague contract disclosures. The clause allowing "additional agreed-upon conditions" in regulatory fatwas was frequently exploited to introduce unjustified fees. These practices compromised the ethical foundation of IULI and undermined the maqasid objectives of wealth protection and justice.ImplicationsThe findings highlight a justice deficit in IULI implementation, signaling the need for stricter governance, transparent disclosure, and ethical oversight. Structural compliance must be complemented by ethical substance to preserve public trust in Islamic finance. This study calls for the institutionalization of maqasid-based performance criteria and regulatory reforms to uphold the values of Shariah in financial products.Originality/NoveltyThis research contributes a novel evaluative framework rooted in Abu Zahrah’s maqasid to assess the ethical validity of Islamic unit-linked insurance. By shifting the evaluative focus from formal legality to ethical substance, the study offers critical insights into aligning Islamic financial practices with the true spirit of Shariah.